Gujarat Board GSEB Textbook Solutions Class 11 Maths Chapter 5 Complex Numbers and Quadratic Equations Ex 5.3 Textbook Questions and Answers.

## Gujarat Board Textbook Solutions Class 11 Maths Chapter 5 Complex Numbers and Quadratic Equations Ex 5.3

Solve each of the following equations:

1. x^{2} + 3 = 0

2. 2x^{2} + x + 1 = 0

3. x^{2} + 3x + 9 = 0

4. – x^{2} + x – 2 = 0

5. x^{2} + 3x + 5 = 0

6. x^{2} – x + 2 = 0

7. \(\sqrt{2}\)x^{2} + x + \(\sqrt{2}\) = 0

8. \(\sqrt{3}\)x^{2} – \(\sqrt{2}\)x + 3\(\sqrt{3}\) = 0

9. x^{2} + x + \(\frac{1}{\sqrt{2}}\) = 0

10. x^{2} + \(\frac{x}{\sqrt{2}}\) + 1 = 0.

Solutions to questions 1 to 10:

1. x^{2} + 3 = 0 â‡’ x^{2} = – 3

âˆ´ x = Â±\(\sqrt{- 3}\) = Â±\(\sqrt{3i}\).

2. 2x^{2} + x + 1 = 0.

Comparing with ax^{2} + bx + c = 0,

a = 2, b = 1, c = 1.

âˆ´ b^{2} – 4ac = 1^{2} – 4.2.1 = 1 – 8 = – 7

âˆ´ x = \(\frac{-b \pm \sqrt{b^{2}-4 a c}}{2 a}\) = \(\frac{-1 \pm \sqrt{-7}}{2.2}\) = \(\frac{-1 \pm \sqrt{7} i}{4}\).

3. x^{2} + 3x + 9 = 0

âˆ´ a = 1, b = 3, c = 9

âˆ´ b^{2} – 4ac = 32 – 4.1.9

= 9 – 36

= – 27.

4. – x^{2} + x – 2 = 0 or x^{2} – x + 2 = 0.

Here, a = 1, b = – 1, c = 2.

âˆ´ b^{2} – 4ac = (- 1)^{2} – 4.1.2

= 1 – 8 = – 7.

âˆ´ x = \(\frac{-b \pm \sqrt{b^{2}-4 a c}}{2 a}\) = \(\frac{-1 \pm \sqrt{-7}}{2.1}\) = \(\frac{-1 \pm \sqrt{7} i}{2}\).

5. x^{2} + 3x + 5 = 0

âˆ´ a = 1, b = 3, c = 5.

âˆ´ b^{2} – 4ac = 9 – 4.1.5 = 9 – 20 = – 11.

6. x^{2} – x + 2 = 0

âˆ´ a = 1, b = – 1, c = 2.

âˆ´ b^{2} – 4ac = (- 1)^{2} – 4.1.2 = 1 – 8 = – 7.

âˆ´ x = \(\frac{-b \pm \sqrt{b^{2}-4 a c}}{2 a}\) = \(\frac{-1 \pm \sqrt{-7}}{2.1}\) = \(\frac{-1 \pm \sqrt{7} i}{2}\).

7. \(\sqrt{2}\)x^{2} + x + \(\sqrt{2}\) = 0

âˆ´ a = \(\sqrt{2}\), b = 1, c = \(\sqrt{2}\).

âˆ´ b^{2} – 4ac = 1^{2} – 4(\(\sqrt{2}\).\(\sqrt{2}\)) = 1 – 8 = – 7.

âˆ´ \(\frac{-b \pm \sqrt{b^{2}-4 a c}}{2 a}\) = \(\frac{-1 \pm \sqrt{-7}}{2 \cdot \sqrt{2}}\) = \(\frac{-1 \pm \sqrt{-7} i}{2 \sqrt{2}}\).

8. \(\sqrt{3}\)x^{2} – \(\sqrt{2}\)x + 3\(\sqrt{3}\) = 0

âˆ´ a = \(\sqrt{3}\), b = – \(\sqrt{2}\), c = 3\(\sqrt{3}\).

âˆ´ b^{2} – 4ac = (- \(\sqrt{2}\))^{2} – 4.\(\sqrt{3}\).3\(\sqrt{3}\) = 2 – 36 = – 34.

9. x^{2} + x + \(\frac{1}{\sqrt{2}}\) = 0, Multiplying by \(\sqrt{2}\), we get

\(\sqrt{2x}\) + \(\sqrt{2x}\) + 1 = 0.

âˆ´ a = \(\sqrt{2}\), b = \(\sqrt{2}\), c = 1.

âˆ´ b^{2} – 4ac = (\(\sqrt{2}\))^{2} – 4.\(\sqrt{2}\).1 = 2 – 4\(\sqrt{2}\).

10. x^{2} + \(\frac{x}{\sqrt{2}}\) + 1 = 0

Multiplying by \(\sqrt{2}\), we get

\(\sqrt{2}\)x^{2} + x + \(\sqrt{2}\) = 0.

âˆ´ a = \(\sqrt{2}\), b = 1, c = \(\sqrt{2}\)

âˆ´ b^{2} – 4ac = 1^{2} – 4\(\sqrt{2}\).\(\sqrt{2}\) = 1 – 8 = – 7.

âˆ´ x = \(\frac{-b \pm \sqrt{b^{2}-4 a c}}{2 a}\) = \(\frac{-1 \pm \sqrt{-7}}{2 \sqrt{2}}\) = \(\frac{-1 \pm \sqrt{7} i}{2 \sqrt{2}}\).